Job Satisfaction of Bankers in Islami Shariah-based Private Commercial Banks of Bangladesh: Application of Job Characteristics Model - Alam, Md. Shahbub; Hawlader, Md. Rasel; Chowdhury, Farjana Yeasmin (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
The study aims to find connections between job satisfaction and different parts of the Job Characteristics Model (JCM) in Bangladesh's non-government Islamic banks. 238 bankers filled out an organized questionnaire for a quantitative research design study. The outcomes were examined using descriptive statistics, multiple regression analysis, correlation analysis, and dependability analysis. The multiple regression analysis shows that the JCM's categories can predict satisfaction well, explaining 59.5% of the total variation. Skill variety, job identity, autonomy, and feedback practices significantly increase job satisfaction, while task significance does not. The most influential factor in determining bankers' job satisfaction was autonomy. The study shows the significance of job characteristics in determining job satisfaction among bankers in Islami Shariah-based Private Commercial Banks. To improve job satisfaction and organizational success, managers and lawmakers should consider making skills more varied, tasks more straightforward, freedom more available, and feedback more available.